(Re)Inhabiting awareness: geography and mindfulness. (18th May 2016) - Whitehead, Mark; Lilley, Rachel; Howell, Rachel; Jones, Rhys; Pykett, Jessica
Abstract: This paper opens up a dialogue between mindfulness and the discipline of geography. As a meditative practice that cultivates 'present-centred non-judgmental awareness', we claim that the practices and insights of mindfulness have important implications for various forms of geographical enquiry. This paper argues that mindfulness can inform geographical practices in relation to epistemology and methodology, and contribute towards geographically informed critical psychological theory and action. More specifically, we claim that mindfulness could offer a practice-based context to support the study of affects, extend the application of psychoanalytical geographical methods beyond the therapeutic, and contribute to emerging geographical studies of behavioural power and empowerment. This analysis explores these sites of interaction through a series of reflections on the Mindfulness, Behaviour Change and Engagement in Public Policy programme that was developed and delivered by the authors. This more-than-therapeutic mindfulness programme has been delivered to approximately 47 civil servants working in the UK Government.